(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Child abuse is a grieved inhuman activity and a moral crime whose outcome is generally visible in the physical, psychological and behavioral growth of the victim. Along with the efforts targeting the end of abusive activities, it is essential to ensure the proper implementation of profound techniques of investigation and their appropriate application while handling of the cases to eliminate the traumatisation for these young victims. Children are comparatively vulnerable and innocent than any other member of society so they deserve greater care, protection and safeguard of their rights and interests. Childhood today is at the risk of several threatening crimes including neglect, maltreatment, abduction, sexual abuse, exploitation, oppression, trafficking, molestation, pornography and several others.